Breaking the Hard Limits: Romance, Pornography, and the Question of Genre in the Fifty Shades Trilogy - McAlister, Jodi (Analyses/Rereadings/Theories: A Journal Devoted to Literature, Film and Theatre, 2015)
The Fifty Shades series has brought erotic fiction to a broader and more mainstream audience than ever before. In its wake, a number of erotic romance series have achieved unprecedented popularity, such as Sylvia Day’s Crossfire series and Lisa Renee Jones’ Inside Out series. These books do not fit comfortably into the genres of romance or pornography: rather, they fuse the romantic and pornographic together. This locates the multiple climaxes of pornography within the overarching emotional climax of romance and creates a structure that is both finite and infinite, allowing the books to create both instant and delayed gratification. This article examines The Sheik as a textual forebear to Fifty Shades before moving on to examine the ways in which romance and pornography are fused, overcoming the limits of serialization in romance, and creating a romantic “pornotopia.”